TINJAUAN KRIMINOLOGIS TERHADAP KEJAHATAN PENCURIAN HANDPHONE DI WILAYAH HUKUM KEPOLISIAN RESOR KUPANG KOTA (STUDI KASUS TAHUN 2020 SAMPAI 2022) - Merukh, Jems; Tallo, Daud Dima; Amalo, Heryanto (Petitum Law Journal, 2023)
Recently in the city of Kupang there are often cases of theft of handphone which greatly disturb the security and public order in the city of Kupang. Therefore, according to the author, it is necessary to take countermeasures. This countermeasure effort is the responsibility of the Kupang City Police because their duties are law enforcement and maintaining order. The purpose of writing this thesis is to find out the factors that cause someone to steal a handphone in the Kupang City Police District Law area and to find out the efforts of the Police in tackling handphone theft in the Kupang City Police District Law area. The research method used is empirical juridical research, namely examining events in the field related to handphone theft, the factors that cause someone to steal a handphone in the Kupang City Police Legal area and the Police's efforts in tackling handphone theft in the Kupang City Police Law area with techniques interviews with members of the police and then the results of the interviews were analyzed qualitatively. The results of the study concluded: The factors of the occurrence of the crime of handphone theft in Kupang City are economic factors, environmental factors and victim negligence factors. As well as the efforts made by the Kupang City Police, namely pre-emptive, preventive and repressive efforts, and it is hoped that the Kupang City government will pay more attention to the welfare of the community by providing employment opportunities, it is hoped that there will be cooperation from the Kupang City Police and the community, increasing the effectiveness of Bhabinkamtibmas, and it is hoped that the Kupang City Police will increase the effectiveness of the disclosure of handphone theft cases.